2017
DOI: 10.1017/iop.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Engagement Apart: The Role of Intrinsic and Extrinsic Motivation in Engagement Strategies

Abstract: Employee engagement has long been an instrumental component of human capital strategies and continues to dominate the conversation about how high-performing organizations attract and retain their best talent. Engagement is a construct of component parts, however, and we believe there is still much to be learned about engagement by taking an in-depthEmployee engagement has long been an instrumental component of human capital strategies and continues to dominate the conversation about how high-performing organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 30 publications
1
43
0
4
Order By: Relevance
“…Moreover, notwithstanding the paucity of studies, motivation and engagement are sought-after qualities in organizations. They are essential to attract and retain talented workers (Delaney and Royal, 2017) and younger generations (Eversole et al, 2012).…”
Section: Purpose and Motivationmentioning
confidence: 99%
“…Moreover, notwithstanding the paucity of studies, motivation and engagement are sought-after qualities in organizations. They are essential to attract and retain talented workers (Delaney and Royal, 2017) and younger generations (Eversole et al, 2012).…”
Section: Purpose and Motivationmentioning
confidence: 99%
“…Initial assumptions were that variables associated with Self-Determination Theory (specifically, intrinsic motivation or amotivation) would more strongly predict engagement (Abós, Haerens, Sevil, Aelterman, & García-González, 2018;Delaney & Royal, 2017;Kaplan & Madjar, 2017;Renninger & Hidi, 2015). However, these variables do not appear to be significant in explaining academic engagement in this sample of future Chilean professors.…”
Section: Discussionmentioning
confidence: 91%
“…The literature has shown that different motivational variables impact students' academic engagement and that this, in turn, influences learning behaviour. For example, studies have used Self-Determination Theory (SDT) (Deci & Ryan, 2012;Ryan & Deci, 2017) to show that intrinsic motivation positively impacts engagement (Froiland & Worrell, 2016), as do extrinsic motives, though to a lesser extent (Delaney & Royal, 2017). In the same vein, lack of motivation negatively impacts academic engagement (King & Datu, 2017).…”
mentioning
confidence: 99%
“…Iako bi se moglo očekivati da će intrinzična motivacija, u usporedbi s ekstrinzičnom motivacijom, imati snažniji pozitivni efekt na učinak zaposlenika (Deci, Ryan, 2000), empirijska istraživanja nisu potvrdila utjecaj intrinzične motivacije na uspjeh u izvršavanju zadataka (Zhang et al, 2016). Kako bi organizacije kod zaposlenika potakle intrinzičnu motivaciju, poželjno je kreirati izazovne i zanimljive poslove koji u potpunosti iskorištavaju i razvijaju njihova znanja i vještine, ukloniti birokraciju i loše osmišljene procese, osnažiti zaposlenike za razvoj novih načina rada temeljem njihovih razlika i jedinstvenih karakteristika te poticati menadžere da odaju priznanje zaposlenicima iznad i ispod u hijerarhijskom lancu (Delaney, Royal, 2017).…”
Section: Intrinzična I Ekstrinzična Motivacijaunclassified
“…Uz ekstrinzičnu motivaciju povezuje se želja da se određena aktivnost izvršava s namjerom da se ostvare pozitivne posljedice, poput nagrada, ili izbjegnu negativne posljedice u vidu kazni (Deci, Ryan, 2000). Ekstrinzična motivacija vođena je formalnim poticajima ili poticajima koji zaposlenicima donose opipljive prinose u obliku nagrada ili statusa, ali i dobivanja visoke ocjene radne uspješnosti, ostvarenje napredovanja, izloženosti višim rukovoditeljima ili vođenja tima ili projekta (Delaney, Royal, 2017).…”
Section: Intrinzična I Ekstrinzična Motivacijaunclassified